Effect of the chemical substitution on structural parameters and microwave properties of the Co–Ni–Zn spinels - D.A. Vinnik; D.P. Sherstyuk; V.E. Zhivulin; S.A. Gudkova; P.A. Zezyulina; D.A. Petrov; A.O. Shiryaev; Yuan Yao; S.V. Trukhanov; T.I. Zubar; A.V. Trukhanov (Journal of Materials Research and Technology)
Co0.3Ni0.7-xZn xFe2O4 (where x = 0.00–0.7 with step 0.1) spinels or CNZF with constant Co concentration and varying of the Ni/Zn concentration were obtained by the ceramic method from initial oxides. Based on X-ray diffraction data it was concluded that all samples are single-phase (SG: Fd-3m). Concentration dependences of the lattice constant and unit cell volume correlate well with Vegard's rule and the average value of the Zn2+ and Ni2+ ionic radii. The microwave permeability was measured in the frequency range of 0.1–20 GHz by a coaxial technique. Two resonances on frequency dependences were observed. Analysis of the microwave properties and magnetostatic data showed that low-frequency magnetic peak was caused by a resonance of domain boundaries; high-frequency peak was due to a natural ferrimagnetic resonance. Obtained results opens broad perspectives for practical application of such kind of materials and possibility for microwave parameters control by the external magnetic field.